Osteochondritis dissecans of the talar dome in patients with tarsal coalition - Karen Y. Cheng (2022)
Objective: Tarsal coalition is known to cause abnormal talocrural stress, hindfoot malalignment, and ankle sprains. These can all be associated with osteochondritis dissecans (OCD) of the talar dome. We present the first detailed description of a series of talar OCDs occurring in patients with tarsal coalition, with the goal of determining whether there is an increased prevalence of OCDs among patients with tarsal coalition. Materials and methods: We studied ankle MRIs in 57 patients with tarsal coalitions, excluding those with a reported inciting traumatic event. The MRIs were performed on magnetic field strengths ranging from 0.3 to 1.5 T and included axial, coronal, and sagittal T1 and T2 or PD fat-suppressed sequences. We evaluated the morphology and location of classically described OCDs in these patients, type and location of concomitant tarsal coalition, and, when available, the presence of pes planus and hindfoot valgus on weight-bearing radiographs. Chi-squared analysis was used to compare categorical variables and a Student’s t test was used for parametric continuous variables. Additionally, logistic regression was used to compute the odds ratio of talar OCD associated with patient age, gender, laterality, pes planus status, hindfoot valgus status, and coalition type. Results: Eighty-nine percent of tarsal coalitions were non-osseous coalitions and the calcaneonavicular space was the most common site of abnormal tarsal connection (54.4%). In the 29 patients with tarsal coalitions and talar OCDs, OCDs commonly occurred medially (75.9%). In the sagittal plane, talar OCDs occurred centrally, with only one case sparing the central talar dome. The mean surface area of the 29 OCDs was 89.7 mm2. Both osseous coalition and hindfoot valgus were associated with smaller talar OCD mean surface area (p = 0.015 and p = 0.0001, respectively). There was no association between depth and surface area of talar OCD with either coalition location or presence of pes planus (coalition location: p = 0.455 for depth and p = 0.295 for surface area; presence of pes planus: p = 0.593 for depth and p = 0.367 for surface area). Conclusion: Talar OCD prevalence is higher in patients with tarsal coalition than that reported for the general population. This occurrence may relate to altered biomechanics and repetitive talocrural stress owing to altered subtalar motion, particularly given the findings of increased odds of talar OCD in older patients, as well as weak associations between OCD surface area and both non-osseous coalition and hindfoot alignment. However, we did not find any specific OCD morphologic features attributable to the precise location of the tarsal coalition.